From Clicks to Trust: Insights into Customer Brand Relationships on TikTok - Pranata, Sungguh Ponten (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to understand how brands can build and maintain trust and strong relationships with customers on TikTok's social media platform. Using an exploratory qualitative approach, data was collected through semi-structured interviews and content analysis of brand activity on TikTok. The results show that customer trust is the main foundation in brand-customer relationships. This trust is formed through consistent communication and credibility, strengthened by positive associations with influencers, and product and service quality. Additionally, the reputation and security features of the TikTok platform also play an essential role in influencing customer purchasing decisions. This research emphasizes that brands need to adopt a holistic approach that includes consistency in communications, appropriate use of influencers, and a focus on platform reputation and credibility to build and sustain customer trust and loyalty on an ongoing basis. This approach is considered essential in achieving success in the dynamic digital era.